Characterization of PVD Cr-C, Cr(C,N) and Cr-N hard coatings - Čekada, Miha (Kovine zlitine tehnologije, 1999)
Cr-N hard coatings have been widely investigated for over 10 years and successfully implemented in industry. Recently work has been done on Cr-C hard coatings and some industrial applications were reported, in particular, the protection of tools for aluminium die-casting. However, information about the ternary Cr(C,N) hard coataings is scarce. We prepared several Cr(C,N) hard coatings with different C:N ratios by varying the ?$N_2$? and ?$C_2H_2$? flow. Stoichiometric, as well as nonstoichiometric Cr-N and Cr-C coatings were prepared for comparison. The coatings were deposited by evaporation in a thermionic arc ion plating BAI730M (Balzers) apparataus. Polished tool steel disks, silicon wafers and polished alumina ceramics were used as substrates. Oxidation of the coatings was carried out by heating the samples at 750-900°C in an oxygen atmosphere while measuring the weight gain and the thickness increase. The depth profiles of the samples, oxidized at various temperatures,were measured by Auger Electron Spectrometer (AES). Microhardness, adhesion and surface roughness were also measured. We investigated the influence of the ?$N_2$? and ?$C_2H_2$? partial pressures on the above mentioned physical and chemical properties. The results show that Cr-C coatings do have the potential for industrial application.
Keywords: kovinske prevleke; krom; nitridi; karbidi; vakuumsko nanašanje; mikrotrdota; adhezija; oksidacija